A Pragmatic Analysis of Evasion in Political Interviews - Mohammed Kadhim Ali Al-Sahlanee; Duaa Abd Al-muhsen Abd Al-Rudaa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
There are common perceptions that politicians use in a very clear way evasion strategies because they are exposed to embarrassing questions which detect their policy. So they use evasion strategies to save their face and to be polite to the audience and voters, and hence, they ensure to be elected and reelected. Accordingly, the present study aims at analyzing evasion strategies in political interviews for four prominent politicians: the former Prime Minister of the United Kingdom and the leader of the Conservative Party Theresa May, the Member of Parliament and leader of the British Labor Party Jeremy Corbyn, the former President of the United States of America Donald Trump and the former US Secretary of State Mike Pompeo.